Marginalised Students’ Funds of Knowledge in Teaching and Learning Science: A Systematic Literature Review - Phillip, Paul Anak; Arsad, Nurazidawati Mohamad (International Journal of Social Science Research, 2024)
Funds of knowledge refer to the historically accumulated and culturally developed bodies of knowledge and skills essential for household and individual functioning and well-being. Teachers face students from different backgrounds in the classroom. In order to provide the best possible education for all the students in a classroom, teaching practices must reflect an authentic sense of caring for a child in a way that recognises the importance of the utilisation of marginalised students’ fund of knowledge. Hence, reviewing existing literature systematically is very important for finding the gaps in using marginalised students’ funds of knowledge in science teaching and learning. A systematic Literature Review (SLR) is conducted to identify the type of funds of knowledge that can be used in science teaching and learning processes. Out of 321 articles identified from Scopus and Web of Science (WoS) databases, 28 articles were selected for the systematic review process. The finding of the analysis shows nine types of funds of knowledge that can be used in teaching and learning science, particularly for marginalised students. This research and its finding are expected to provide insight and information on the type of funds of knowledge for marginalised students that can be utilised in science education and contribute to the improved quality of science education in general.